SIKAP PETANI DALAM PENGEMBANGAN KAPASITAS PRODUKSI PADI ORGANIK DI KOTA BINJAI PROVINSI SUMATERA UTARA - Tience Elizabet Pakpahan (JURNAL AGROTEKNOSAINS, 2020)
The Attitude of Farmers in Increasing the Capacity of Organic Rice Production in the city of Binjai. This study aims to analyze the level of attitude of farmers and influcung factors in increasing the capacity of organic rice production in the city of Binjai. Primary data obtained from 41 farmers using a questionnaire that has been compiled. The analysis used in this study is multiple linear regression analysis using the Statistical Product Service Solution (SPSS) program version 16. Secondary data were obtained from agencies related to this research, namely the Department of Agriculture and Food Crops of Binjai City. The location of the final project activity is in Binjai City and the implementation time is from March  - May 2020.  The results of this study indicate the level of farmers' attitudes in increasing the capacity of organic rice production in the very high category 91.05%. Variable factors that influence the level of farmers' attitudes in developing organic rice production capacity, are obtained equations as followsbn namely, knowledge variables with regression coefficient (0.162), farming experience (0.201), land area (0.231), capital ownership (0.255), access to production facilities (0.191). ), technology (0.255), and market variables (0.187). Overall, the assessment variables had a significant and very significant effect on farmers' attitudes in developing organic rice production capacity, which had a very dominant effect is the capital ownership variable.